Los Alamos wildfires - Bryan, Nichol (Milwaukee, WI : World Almanac Library, 2004)
Describes the events surrounding the wildfire that raged in New Mexico in 2000 and the resulting debate over the policy of prescribed burning, or purposely setting fires as a means of forest management.
Introduction: Fire storm -- Fighting fire with fire -- Begging to burn -- "It should never have happened" -- Learning to live with fire -- Time line -- Glossary -- For more information/Web sites -- Index.
10 - 12 years
Keywords: Wildfires -- New Mexico -- Los Alamos Region; Prescribed burning -- New Mexico -- Los Alamos Region; Wildfires -- New Mexico; Prescribed burning; Forest fires; Fires -- Los Alamos Region (N.M.)